2021
DOI: 10.2174/1874434602115010262
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Coping Strategies among Nurses during the COVID-19 Pandemic: A Cross-Sectional Online Survey

Abstract: Background: The emergence of COVID-19 has a significant impact on nurse’s overall health. The severity and magnitude of the COVID-19 pandemic means it is extremely likely that health-care professionals will experience psychological distress as a result of their direct contact with patients who have contracted the infection. Objectives: This study aimed to evaluate levels of psychological distress among nurses during the COVID-19 pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Finally, in the study conducted by Alnazly and Hjazeen [30] in Jordan, a mean score for the FCV-19 of 24.34 was obtained, indicating a remarkable fear of the COVID-19 pandemic. Female nurses were also found to have a higher mean score for fear of COVID-19 than their male counterparts [30].…”
Section: Fearmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, in the study conducted by Alnazly and Hjazeen [30] in Jordan, a mean score for the FCV-19 of 24.34 was obtained, indicating a remarkable fear of the COVID-19 pandemic. Female nurses were also found to have a higher mean score for fear of COVID-19 than their male counterparts [30].…”
Section: Fearmentioning
confidence: 89%
“…Finally, the study by Alnazly and Hjazeen [30] also used the DASS scale, concluding that 73.8% of the sample had an extremely severe level of anxiety, 43.8% had a moderate level of depression, and 45.4% had a severe level of stress [30].…”
Section: Anxiety Depression and Stressmentioning
confidence: 99%
“…Alnazly and Hjazeen’s study showed that nurses had moderate levels of anxiety (mean score: 24.34 ± 13.43) and depression (43.8% of the sample) and severe anxiety (73.8%) and stress (45.4%). Nurses who cared for patients who tested positive for coronavirus in 2019 and those who had friends or family members who tested positive had higher levels of anxiety and distress ( p < 0.001 and p = 0.010) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each factor has two items, and the total scores on each can range from 2 to 8, with higher scores indicating more significant use of coping strategies. The Brief COPE's validity has been assessed in multiple nursing studies, and its reported alpha coefficients have ranged from 0.81 to 0.88 in previous studies (Abdul Rahman et al., 2021 ; Alnazly & Hjazeen, 2021 ). We used the Iranian version of the Brief COPE, which had adequate internal consistency reliability (α = 0.77), and the intra‐class correlation coefficient was reported as acceptable for scale ( r = 0.76) (Ashktorab, et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%